Contralateral compartment syndrome inoculated by invasive group A streptococcus. Issue 5 (1st January 2016) - Chen, Huiwen; Mcphillips, Sean Thomas; Chundi, Vishnu
Abstract : Compartment syndrome is a rare but a well-documented complication in patients with trauma-induced group A streptococcus infection. Here, we present a case of a male who developed compartment syndrome on the left lower extremity after an injury inoculated by group A streptococcus on the right lower extremity. The patient was resuscitated with antibiotics, urgent fasciotomy, and immunoglobulin. The patient was eventually transferred to a burn center for further care.